ANALISIS PENGUNGKAPAN SUSTANINABILITY REPORT BERDASARKAN GRI INDEKS PADA PT.INDOFOOD CBP SUKSES MAKMUR DAN PT. UNILEVER INDONESIA - Muhammad Hidayat; Jasmine Afifah; Catur Fatchu Ukhriyawati (Universitas Riau Kepulauan, 2022)
AbstractThis research was conducted to find out how the application of sustainability reports in the company's annual reports and make a comparison of how the level of application is in two large companies listed on the Indonesia Stock Exchange in the consumer goods industry sector in 2021. The object of this research is PT. Indofood CBP Sukses Makmur and PT. Unilever Indonesia, with the variable in this study is the level of compliance in disclosing the sustainability report The data used in this study was secondary data in the form of company annual reports taken directly from the company's website which is the object of research. The author uses the GRI index as an indicator in the implementation of the sustainability report and uses content analysis and comparative methods as analytical tools. The results showed that the level of disclosure compliance in the Indofood CBP Sukses Makmur sustainability report was classified as partially applied and PT. Unilever Indonesia is also classified as partially applied. In addition to seeking economic benefits, the two companies also deal with the impacts arising from the company's activities.